Biomechanical assessment of unilateral/bilateral lumbar spondylolysis with and without muscle weakness using finite element analysis - Baiyang Ding; Kazuhiro Imai; Zhuo Chen; Liang Xiao (Heliyon)
Background: Spondylolysis is commonly linked to low back pain in athletes, and the connection between muscle weakness and spondylolysis is unclear. Therefore, this study examined the biomechanics of spondylolysis and influence of muscle weakness by finite element (FE) analysis. Methods: A patient's L1–S1 lumbosacral unit was scanned by computed tomography, and generated a three-dimensional pathology-free FE model. Unilateral incomplete, unilateral, and bilateral defect models of the L5 isthmus were created. The mobility of the sacrum was limited to 7.5 N m moment, and a 500 N load was applied to the top of the L1 to simulate the human weight. The loading conditions included flexion, extension, bending, and axial torsion. Muscle forces representing the global back muscles and abdominal muscles, follower loads, and body weight were added to the FE model. The force of the global back muscles was decreased to 50 % to simulate back muscle weakness. Findings: The result shows that the L5 vertebral body in unilateral incomplete lumbar spondylolysis exhibited the greatest range of motion during flexion. The L5 vertebral body in unilateral lumbar spondylolysis demonstrated increased mobility during flexion and right torsion. The reduction of muscle strength led to the range of motion of L5 being reduced in all motions, but the maximum principal stress did not change significantly. However, the range of motion and maximum principal stress of L4 increased, especially in the bilateral group. Interpretations: From a biomechanical perspective, this study indicates that unilateral incomplete spondylolysis and unilateral spondylolysis might worsen during different motions. The reduction of muscle strength can cause spondylolysis to spread to adjacent segments and further worsen. A decrease in muscle force led to a decrease in the range of motion in the lumbar spondylolysis defect, but it also led to an increase in the range of motion in the adjacent segments.